Developing Early Career Researchers’ Self-efficacy for Academic Writing - McLellan, Gillian; Smith, Michelle; Hardy, Alison; Murray, Rowena; Thow, Morag (Journal of Academic Writing, 2024)
Self-efficacy is important for maintaining a person’s belief in their capacity to perform desired behaviours and achieve desired goals; without self-efficacy, in the context of academic writing, one may doubt their ability to achieve writing goals. Previous research showed that the Writing Meeting Framework (WMF) can enable desired changes in writing behaviours but did not consider the role of self-efficacy in this behaviour change. This UK-based study aimed to determine if the WMF could improve writing self-efficacy for postgraduate researchers (PGRs) and early career researchers (ECRs). Participants completed a baseline questionnaire to reflect on their writing experiences and then were randomly matched into 35 pairs. Each pair met online four times over eight weeks using the WMF and then completed a post-questionnaire, reflecting on their experiences. Analysis showed significant improvements in self-efficacy using the WMF: participants improved their ability to set realistic and achievable writing goals and increased their confidence in completing writing goals regularly. This study shows the WMF can develop PGRs’ and ECRs’ academic writing self-efficacy and suggests the WMF can develop writing attributes required to produce academic writing regularly and achieve individual writing goals. The WMF offers a mechanism for developing this important component of effective writing behaviour.